The emotional effects of colors in the industrial product (Journal of the College of Basic Education, 2022)
Emotional design research is considered one of the new and important research in product design, because of the different cultural and social nature of the user, so conducting this type of research is beneficial for both the user and the designer, as it determines the acceptability and marketing of the industrial product. The research problem was the following question: How to reveal the preference Colors and their emotional associations in the industrial product? While the limits of the research were designing a chair in seven primary and secondary colors, in addition to choosing 7 emotional vocabulary, and 101 male and female students in the design department were surveyed for arriving at results.The most important results were:1- It was shown the preference for cold colors in industrial products, primarily violet and then blue.2- Positive emotional vocabulary of cold colors, on top of which was (attractive), blue and violet in the foreground.3- Cold colors in total had the highest preference for positive emotional vocabulary, while warm colors were negative